El conocimiento en la sociedad medial y relación educativa - Desimone, Giuseppe; Annarumma, Maria (Studi sulla Formazione/Open Journal of Education, 2019)
The current society, "liquid", "complex" and "postmodern", requires that educators provide the keys to interpret reality and to orientate their actions in a democratic perspective. The educational relationship can produce comparison between multiple languages and develop a "structural criticality".